1979
DOI: 10.1111/j.1365-2230.1979.tb01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Letterer-Siwe disease in an elderly patient: histological and ultrastructural findings

Abstract: Summary A 91‐year‐old woman presented with an itchy, erosive and scaly eruption of about 2 years duration. Clinical, histological and ultrastructural examination of the skin lesions showed typical changes due to Letterer‐Siwe disease. Large mononuclear cells with deeply idented or convoluted nuclei and with Langerhans' cell granules in the cytoplasm, were found to invade the superficial dermis, epidermis and dermo‐epidermal junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…16,17,18,19,20 Electron microscopic studies show that approximately 50% of the histiocytes (LCs) of the LCH contain Birbeck granules in their cytoplasm. 23,24,25 Birbeck granules (gs) are peculiar membrane-bound rod or tennis racket shaped inclusions with a central, linear, longitudinally striated nucleus found in the cytoplasm of the LCs of the epidermis; they are also called Langerhans' gs and vermiform gs. 26 Some authors have suggested 27 that histologic features are correlated with prognosis in LCH.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,18,19,20 Electron microscopic studies show that approximately 50% of the histiocytes (LCs) of the LCH contain Birbeck granules in their cytoplasm. 23,24,25 Birbeck granules (gs) are peculiar membrane-bound rod or tennis racket shaped inclusions with a central, linear, longitudinally striated nucleus found in the cytoplasm of the LCs of the epidermis; they are also called Langerhans' gs and vermiform gs. 26 Some authors have suggested 27 that histologic features are correlated with prognosis in LCH.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are commonly seen within the infiltrate. Eady (1979) suggests that the mononuclear cell morphology is more clearly defined in semithin plastic sections.…”
Section: Discussionmentioning
confidence: 99%
“…In four of the seven cases in which electron micrographs were obtained, the characteristic 'X' granules were demonstrated (Eady, 1979). In most instances the infiltrate consisted only of histiocytes, but in some biopsies were was a sparse admixture of eosinophils and lympho-0307-6938/79/1200-0407 J02.00…”
Section: Histopathologymentioning
confidence: 94%